Hearing, Speech, Language, and Communicative Participation in Patients With Apert Syndrome: Analysis of Correlation With Fibroblast Growth Factor Receptor 2 Mutation. Issue 1 (23rd January 2022) - Kilcoyne, Sarah; Luscombe, Carrie; Scully, Paula; Overton, Sarah; Brockbank, Sally; Swan, Marc C.; Johnson, David; Wall, Steven; Wilkie, Andrew O.M.
Abstract : Supplemental Digital Content is available in the text Abstract : Apert syndrome (AS) is caused by the heterozygous presence of 1 of 2 specific missense mutations of the fibroblast growth factor receptor 2 ( FGFR2 ) gene. The 2 adjacent substitutions, designated p.Ser252Trp (S252W) and p.Pro253Arg (P253R), account for more than 98% of cases. Previous research has identified elevated hearing difficulties and incidence of cleft palate in this population. However, the influence of FGFR2 genotype on the speech, language, and communicative participation of children with AS has yet to be examined. Methods: A retrospective case note analysis was completed for all patients with a genetically-confirmed Apert mutation who attended the Oxford Craniofacial Unit over a 43-year period (1978–2020). Medical records were analyzed for speech, language, hearing, and communication data in detail. The therapy outcome measures, based on the World Health Organization International Classification of Functioning, Disability, and Health was used to classify patient's communicative participation. Results: The authors identified 55 AS patients with genetically-confirmed mutation of the FGFR2 gene. One patient with a S252F mutation was excluded. There were 31 patients with the S252W mutation (male = 14; female = 17), age range of last hearing assessment (1–18 years), 64% (18/28) of patients had a cleft palate (including bifid uvula), 15 patients had conductive hearing loss, 1 patient had mixed hearing loss, 18 had otitis media with effusion (4 of whom had a cleft palate); 88% (21/24) of patients had receptive language difficulties, 88% (22/25) of patients had expressive language difficulties, 96% (27/28) of patients had a speech sound disorder. There were 23 patients with the P253R mutation (male = 13; female = 10); age range of last hearing assessment (1–13 years), 35% (8/23) patients had a cleft palate (including bifid uvula), 14 patients had a conductive hearing loss, 17 had otitis media with effusion (2 of whom had a cleft palate). Results indicated that 85% (17/20) of patients had receptive language difficulties, 80% (16/20) had expressive language difficulties, 100% (21/21) had a speech sound disorder. The S252W mutation was significantly-associated with the presence of cleft palate (including bifid uvula) ( P = 0.05). Data about the cumulative impact of all of these factors for communicative participation using the therapy outcome measures were available for 47 patients: (30 S252W; 17 P253R). Patients with a S252W mutation had significantly more severe difficulties with communicative participation when compared to individuals with a P253R mutation ( P = 0.0005) Cochran-Armitage trend test. Conclusions: Speech, language, communicative participation, and hearing difficulties are pervasive in patients with AS. The severity and functional impact of these difficulties are magnified in patients with the S252W mutation. Results reinforce the importance of considering patients with AS according to genotype.